The role of struggles in combating depression and anxiety: An integrative review (Research, Society and Development, 2023)
Analyze, based on literature, the role of struggles in combating depression and anxiety. This is an integrated review of the literature, carried out by searching for studies in national and international databases: Latin American and Caribbean Literature in Health Sciences (LILACS), Nursing Database (BDENF) and Medical Literature Analysis and Retrieval System Online (MEDLINE). The final sample consisted of 4 published studies. Results and Discussions: After crossing the definitions and applicability of the inclusion and exclusion process, a discussion was held based on 4 studies. It is concluded that martial arts have the potential to play a significant role in promoting mental health and combating depression and anxiety. However, it is essential that individuals interested in fighting seek appropriate guidance and consider it as part of a comprehensive mental health care plan. Furthermore, more research and studies are needed to deepen our understanding of the benefits of martial fighting in this context.